Numerical study on dimensions and orientation effect of semi-elliptical cracks in PE100 pipelines - Zitouni, T.A.; Labed, Z. (Zielona Góra: Uniwersytet Zielonogórski)
The through-thickness crack or surface crack in PE100 pipes subjected to internal pressure represents a serious risk to the structural integrity of HDPE pipes, which has attracted wide attention in modern industry.
Keywords: pipelines; PE100; semi-elliptical crack; stress concentration; HDPE